Humic Substances from Manila Bay and Bolinao Bay Sediments - Llaguno, Elma (Science Diliman: A Journal of Pure and Applied Sciences; Vol 9, Nos 1 & 2 (1997), 2007)
The C,H,N composition of sedimentary humic acids (HA) extracted from three sites in Manila Bay and six sites in Bolinao Bay yielded H/C atomic ratios of 1.1-1.4 and N/C atomic ratios of 0.09 - 0.16. The Manila Bay HA's had lower H/C and N/C ratios compared to those from Bolinao Bay. The IR spectra showed prominent aliphatic C-H and amide I and II bands. Manila Bay HA's also had less diverse molecular composition based on the GC-MS analysis of the CuO and alkaline permanganate oxidation products of the humic acids.